Restoration of Ecological Management Practices among Keys Attractions in 2nd District of Albay: A Basis for Sustainable Tourism Operations - Longaza, Justin (JPAIR Multidisciplinary Research, 2023)
Restoration of Ecological Management Practices involves activities for the accessibility and protection of Tourist Attraction sites and the benefits of stakeholders for sustainability and development. This study dealt with restoring the environment and health safety, restoring increasing problems concerning natural calamities in the Tourist Attraction sites in the Second District of Albay, particularly in Manito, Daraga, Legazpi City, and Camalig. The data gathered were analyzed and interpreted employing the mixed method of research. Descriptive quantitative was used to analyze the data collected through the use of a questionnaire, constructed interviews to validate gathered data, and analysis of reports and documents. The study revealed the relevance and benefits of Eco-Tourism Management and Sustainability as they proposed Eco-Tourism Plans and activities to address the issue. Analyzed data revealed an Average level of awareness using given variables as proven and identified. Furthermore, there was a Moderate Impact on Indicator: Eco-Tourism Management Sustainability of Ecotourism with fully practiced and practiced. Tourist Sports owners and people in the community demand environmental awareness to protect Tourism Destinations in Albay, particularly in the Second District, as well as the other forms of maintaining Tourist Attractions. Tourism activities vary depending on stakeholders and government officials managing the activities.
Keywords: Social Science; Ecological Management Practices; Restoration; Sustainable Tourism Operation; Philippines